The ultimate guide : volcanoes (Silver Spring, Md : Discovery Channel, 2003)
Looks at ways and means volcanologists predict volcanic eruptions. Watch as they put those theories to the test at the summit of smoldering Mount Tungurahua in Ecuador. It's a high-stakes game of man versus the mountain; because if any of these theories prove correct, they could help forecast future volcanic activity and save lives all over the planet.